Same degree but different outcomes: An analysis of labour market outcomes for native and international PhD students in Australia - Massimiliano Tani (Journal for Labour Market Research, 2022)
This paper used data on career destinations over the period 1999-2015 to study the labour market outcomes of native and foreign PhD graduates staying on in Australia as skilled migrants. Natives with an English-speaking background emerge as benefiting from positive employer 'discrimination' (a wage premium unrelated to observed characteristics such as gender, age, and previous work experience). The premium is field-specific and applies to graduates in Science, Technology, Engineering and Mathematics (STEM). In contrast, foreign PhD graduates with a non-English speaking background experience inferior labour market outcomes, especially if they work in the university sector. Against expectations to the contrary, completing the highest degree of education in the host country and staying on in the same sector where one acquired human capital does not appear to eliminate lesser labour market outcomes for the foreign-born.
Keywords: I26; J24; J31; J61; 330; PhD graduates; Wage decomposition; Discrimination; International students